Estudo de um retificador trifásico Boost operando no MCD com aplicação em geração eólica de pequeno porte - Soltoski, Julio Cesar Ferreira (2016)
This project was developed based on a converter topology proposed in 1994 that has good features for energy conversion application nowadays. The studied rectifier in this paper has application in small wind energy generation that can be connected to DC microgrids, technology that is being researched and studied today. This paper includes theoretical analysis, numerical simulation and experimental data acquisition from a built prototype. In the end, this converter presented satisfying results considering the specification and conditions that the model was exposed. The project specification is the following: input voltage of 48 V, output voltage of 250 V, output power of 1000 W and switching frequency of 20 kHz.